2016
DOI: 10.1007/s00223-016-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive Eating Disorders and Skeletal Health in Adolescent Girls and Young Women

Abstract: This article reviews the effects of restrictive eating disorders on bone health. The relationship between eating disorders and amenorrhea is discussed in detail. The pathologic impact of malnutrition on bone is explored by examining the results of studies using various available imaging techniques. The multiple hormonal alterations seen in adolescents and young women with anorexia nervosa are reviewed, as well as how these alterations may influence bone turnover, density, structure, and strength. The diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 107 publications
0
7
0
1
Order By: Relevance
“…Nutritional status in terms of extremes of underweight and overweight have adverse consequences for bone accretion and development of optimal bone strength. Adolescents with anorexia have low bone density and reduced strength compared to normal weight peers, and these effects can be long lasting (79,80). At the other end of the spectrum, children with obesity have greater bone mineral content and density and greater cortical thickness than non-obese children (81).…”
Section: Diet and Nutritional Statusmentioning
confidence: 99%
“…Nutritional status in terms of extremes of underweight and overweight have adverse consequences for bone accretion and development of optimal bone strength. Adolescents with anorexia have low bone density and reduced strength compared to normal weight peers, and these effects can be long lasting (79,80). At the other end of the spectrum, children with obesity have greater bone mineral content and density and greater cortical thickness than non-obese children (81).…”
Section: Diet and Nutritional Statusmentioning
confidence: 99%
“…Oestrogen affects iron status via hepcidin, and menopausal women often present with iron overload (42,43). Moreover, oestrogen can also directly affect bone metabolism (44,45). It is suggested that oestrogen may participate in the correlation between OP and iron status.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that sedentary behavior, obesity, and eating disorders can contribute to low bone mineral density in adolescents and are important risk factors for adolescent bone health ( Pelegrini et al, 2020 ; Zuckerman-Levin et al, 2014 ; Pollock, 2015 ). Female adolescents may be at greater risk for bone health as most adolescent girls do not meet physical activity guidelines and are more likely to have an eating disorder ( Treuth et al, 2007 ; Bland et al, 2020 ; Thornton and Gordon, 2017 ). Therefore, it is important to take care of adolescent bone health issues, especially for female adolescents.…”
Section: Introductionmentioning
confidence: 99%